SCIENTIFICALLY BASED RECOMMENDATIONS FOR INCREASING THE EFFICIENCY OF REAL ESTATE USE AT THE REGIONAL LEVEL - Kondratiuk, I. (Municipal economy of cities. Series: «Economy science», 2024)
It is proved that real estate is an essential element affecting the functioning of regions, as its use forms the material basis of regional development. In recent years, there has been a decrease in the efficiency of real estate use at the regional level. In this context, we should note the negative impact of external and internal factors and the consequences of Russian aggression. Therefore, theoretical provisions regarding the definition of real estate need further improvement, considering international experience. In addition, the approach to applying the method and models for forming a quantitative basis for real estate use to develop relevant scientifically based recommendations needs reconsideration. The research has achieved the goal of developing scientifically based recommendations for increasing the efficiency of real estate use at the regional level. We have solved the following tasks in the article: substantiating theoretical provisions regarding the definition of regional real estate, forming directions for improving the efficiency of real estate use at the regional level, and proposing a mechanism for using real estate. Real estate is defined as a set of land plots and other objects located on it, forming spatial support from above and below, the use of which has a long-term nature and the movement of which leads to a violation of their functional characteristics. Spatial, functional, investment, and environmental factors influence the formation and use of real estate. Their interaction and definition allow building a multi-level system of assessment indicators to form a quantitative basis for making informed decisions. To increase the level of real estate use in the regions, we have further developed methodological approaches, as recommendations, to the assessment of real estate use based on methods and models that characterise the directions and features of the use of spatial, functional, investment, and environmental support, which provide the opportunity to form a mathematical basis and identify the appropriate toolkit for developing a method for assessing the level of real estate use in regions. Of particular importance are the results of mathematical modelling of real estate use processes at the regional level based on the establishment of relationships between systemic spatial, functional, investment, and environmental factors and an integral indicator by applying the method of correlation-regression analysis, model adequacy criteria, which allows determining directions for increasing the efficiency of use of the real estate. A mechanism for the use of real estate at the regional level is proposed based on the results of the assessment, mathematical modelling, and forecasting of the factors of real estate use, which, unlike the existing ones, made it possible to determine the directions of implementation of scientifically based recommendations and build geospatial monitoring maps. As a result of the study, we have developed a mechanism for real estate use at the regional level as a comprehensive tool for ensuring the efficiency of real estate use in the regions.